Republic of Belarus : 2007 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Belarus. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Belarus's centralized economy grew rapidly over the past few years, enhancing social development. The state redistributed large and growing terms-of-trade gains stemming from favorable Russian energy pricing across the economy, boosting domestic demand. A new energy agreement, however, has abruptly reversed terms-of-trade gains. Belarus now pays Russia twice as much for gas supplies as in 2006 and a fifth more as a share of world market prices for crude oil. This resulted in an estimated loss of 5 1\2 percent of GDP in 2007.